Argument Structure Development in Bahasa Indonesia: How Bilingual Indonesian-Javanese Children (Ages 4-6) Construct Transitive Verbs in Natural Conversation - Elok Nur Affah Al Akromi (Jurnal Indonesia Sosial Teknologi, 2026)
Bilingual children navigate complex linguistic systems while acquiring argument structures in their developing languages. Indonesian-Javanese bilingual children face unique challenges in constructing transitive verbs due to structural differences between these languages, particularly in word order flexibility and affix usage. Understanding how these children develop argument structure competence provides insights into bilingual language acquisition processes. This study investigates how Indonesian-Javanese bilingual children aged 4-6 construct transitive verbs in Bahasa Indonesia during natural conversations, examining patterns of argument realization, word order preferences, and cross-linguistic influence from Javanese. A qualitative longitudinal approach was employed, collecting 60 hours of naturalistic conversational data from 15 bilingual children in Central Java over six months. Conversations with parents, siblings, and peers were video-recorded in home settings. Transitive verb constructions were transcribed, coded, and analyzed using argument structure frameworks. Results reveal three developmental stages: (1) incomplete argument structures with frequent object omission (ages 4-4.5), (2) emerging full transitivity with word order variation (ages 4.5-5.5), and (3) consistent transitive patterns with appropriate affixation (ages 5.5-6). Javanese influence appeared primarily in pronoun usage and word order flexibility rather than core argument structure. Findings contribute to understanding bilingual argument structure acquisition and inform language education policies for Indonesian multilingual contexts, suggesting that transitive verb instruction should accommodate developmental stages and cross-linguistic transfer patterns in early childhood education. In conclusion, Indonesian-Javanese bilingual children follow a systematic developmental trajectory in acquiring transitive verb argument structures in Bahasa Indonesia. Although bilingual children may experience slight delays compared to monolingual norms, their developmental.